2020
DOI: 10.1002/advs.202002157
|View full text |Cite
|
Sign up to set email alerts
|

Nidogen 1‐Enriched Extracellular Vesicles Facilitate Extrahepatic Metastasis of Liver Cancer by Activating Pulmonary Fibroblasts to Secrete Tumor Necrosis Factor Receptor 1

Abstract: In hepatocellular carcinoma (HCC) patients with extrahepatic metastasis, the lung is the most frequent site of metastasis. However, how the lung microenvironment favors disseminated cells remains unclear. Here, it is found that nidogen 1 (NID1) in metastatic HCC cell‐derived extracellular vesicles (EVs) promotes pre‐metastatic niche formation in the lung by enhancing angiogenesis and pulmonary endothelial permeability to facilitate colonization of tumor cells and extrahepatic metastasis. EV‐NID1 also activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 63 publications
1
55
0
Order By: Relevance
“…Moreover, cathepsin degradation of Nid-1 is strongly associated with NSCLC [ 7 ]. Mao et al reported that NID1-enriched extracellular vesicles derived from HCC cells facilitate colonization of tumor cells and extra-hepatic metastasis by activating pulmonary fibroblasts to secrete TNFR1 [ 8 ]. Our study showed that NID1 expression was significantly higher in glioblastoma, anaplastic astrocytoma, and oligodendroglioma compared to the normal brain tissues and cells using glioma datasets from Oncomine, UALCAN, and GEPIA databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, cathepsin degradation of Nid-1 is strongly associated with NSCLC [ 7 ]. Mao et al reported that NID1-enriched extracellular vesicles derived from HCC cells facilitate colonization of tumor cells and extra-hepatic metastasis by activating pulmonary fibroblasts to secrete TNFR1 [ 8 ]. Our study showed that NID1 expression was significantly higher in glioblastoma, anaplastic astrocytoma, and oligodendroglioma compared to the normal brain tissues and cells using glioma datasets from Oncomine, UALCAN, and GEPIA databases.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an urgent need to identify new and more effective therapeutic targets in gliomas. The abnormally high expression of NID1, which is widely discussed in various types of other cancers including ovarian cancer, non-small cell lung cancer and hepatocellular carcinoma [ 6 8 ], in glioma is uncovered through the differently expressed genes (DEGs) analysis between normal and cancer of brain/central nervous system (CNS). However, not many studies on the role of NID1 in glioma are available, and thus we are interested in whether its function in glioma is the same as in other cancer types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yokota, Y. et al determined that HuH-7M (highly intrahepatic metastatic cell line) derived exosomal miRNAs (miR-638, miR-663a, miR-3648, and miR-4258) downregulated ECs expression of ZO-1 and vascular endothelial-cadherin (VE-cadherin) and increased vascular permeability to promote intrahepatic tumorigenesis ( Yokota et al, 2021 ). Additionally, Mao, X. et al found that metastatic HCC cell-derived exosomal nidogen 1 (NID1) activated lung fibroblasts to facilitate tumor extrahepatic metastasis via enhancing angiogenesis and pulmonary endothelial permeability ( Mao et al, 2020 ). In melanoma, exosomes highly expressing urokinase plasminogen activator receptor (uPAR) were internalized by ECs, thus enhancing VE-Cadherin, EGFR, and uPAR expression and pro-angiogenic effects ( Biagioni et al, 2021 ).…”
Section: Exosomes Induce Angiogenesis and Vascular Permeability In Pmnmentioning
confidence: 99%
“…Preclinical trials demonstrated the role of EVs in migration, invasion, and metastasis of HCC. Nidogen 1-enriched EVs have been reported to induce pulmonary fibroblasts to secrete tumor necrosis factor receptor 1, resulting in accelerated extrahepatic metastasis[ 70 ]. Similar findings on the functional role of exosomal miR92a-3p in promoting epithelial-mesenchymal transition and metastasis were found by regulating the Akt/Snail signaling pathway[ 71 ].…”
Section: Blood-based Biomarkersmentioning
confidence: 99%